1997
DOI: 10.1002/aic.690430626
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and data comparison of a supercritical water oxidation reactor

Abstract: Supercritical water oxidation of isopropyl alcohol was investigated in a pilot-scale reactor. A computationalfluid-dynamics model developed reveals the detailed flow field, chemical-component distribution, temperature distribution, and salt-particle trajectories in the reactor flow domain. The near-wall fluid temperature from the numerical analysis was compared with experimental temperature data. The temperature comparison was within a 3% error band. The effect of the chemical kinetic rate was investigated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Previous studies indicate that the RNG k‐ε turbulence model is more accurate to describe the flow recirculation and vortex shedding situations than the standard k‐ε turbulence model. The RNG k‐ε model was thus chosen as the turbulence model in the present study.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicate that the RNG k‐ε turbulence model is more accurate to describe the flow recirculation and vortex shedding situations than the standard k‐ε turbulence model. The RNG k‐ε model was thus chosen as the turbulence model in the present study.…”
Section: Model Descriptionmentioning
confidence: 99%
“…CFD techniques have been applied by several authors to obtain detailed information in SCWO reactors. The CFD simulation of the SCWO process for a MODAR reactor was first developed by Oh et al Zhou et al incorporated the SUPERTRAPP code for thermophysical properties of hydrocarbon mixtures . Moussière et al conducted a simulation using two reaction kinetics models, and the results showed that both models were in general agreement with the experimental data; the Eddy Dissipation Concept approach predicts more accurate temperature peak locations inside the reactor .…”
Section: Introductionmentioning
confidence: 99%
“…In most of CFD works (see Table 4), both characteristic times are calculated and the slowest process is assumed as dominant. Using this approach, Oh et al [111] identified the zones of their reactor where the reaction is chemistry or mixed controlled. They affirm that the mixing zone downstream of the nozzle where the fluids are mixed is chemical-kinetics limited, and outside of this mixing zone the reaction is diffusion limited.…”
Section: Modeling Of Scwomentioning
confidence: 99%
“…This spike of water's properties near the critical condition can result in numerical instabilities, so approximate curves were used instead of the peak near the water's critical point [5] .…”
Section: Turbulence and Reactionmentioning
confidence: 99%
“…Early CFD simulations of a steady-state SCWO process were published by Oh [5] and Zhou [6] . Their work describes flow characteristics of SCWO in the tubular reactor.…”
Section: Introductionmentioning
confidence: 99%